Deformitas Ligula Larva Tanypodinae sebagai Indikator Pencemaran Logam Berat di Danau Lido, Jawa Barat - Tyas Dita Pramesthy; Yusli Wardiatno; Majariana Krisanti (Institut Pertanian Bogor, 2014)
As one group of Chironomidae Tanypodinae larvae can be used in biological assessment to detect the heavymetal pollution in aquatic environment, because they could show morphological changes due to the pollution. Thestudy was aimed to describe ligula deformities in Tanypodinae larvae in a heavy metal polluted lake. The study wasconducted in Mei to June 2014 at Lake Lido, West Java. The results showed that lead (Pb) concentration in LidoLake was quaite high, i.e. 0.08 0.19 mg/L. Ten of fifty-five collected Tanypodinae larve exhibited deformation in theirligulae. Index of severity of ligula deformation (ILSD) was 4.4 indicating the response of the Chironomidae larvae tolead pollution.